PENERAPAN GAME PUZZLE SEBAGAI MEDIA BELAJAR UNTUK MENINGKATKAN MINAT BELAJAR MATEMATIKA PADA KELAS II SDN 153 PEKANBARU - Yespa Warinta; Sakban; Deprizon; Cici Saputri (Jurnal Payung Sekaki : Kajian Keislaman, 2025)
Education is designed with a pleasant atmosphere to achieve learning objectives. This is intended to create active, potential, and morally upright students, because education is the most important means of improving human resources. One of the subjects in elementary school is mathematics because it is related to everyday life. However, most students consider mathematics a difficult subject, resulting in low learning interest. This study aims to increase interest in learning mathematics in second-grade students at SDN 153 Pekanbaru. This study used classroom action research (CAR) with a quantitative approach. The subjects who became respondents in this study were second-grade students at SDN 153 Pekanbaru. The subjects were in the very high category, which increased significantly from 2.7 to 4.7. This study shows that the application of puzzle games as a learning medium successfully increased interest in learning mathematics for students. This puzzle game also sharpens brain intelligence, thinking skills, and serves as a reminder for children.